Comprehending Non-Litigative Resolution of Construction Disputes Through Arbitration - Niniek Lannyati; Samian (Dinasti Research, 2025)
Construction projects are inherently complex, and involve multiple stakeholders with diverse interests and goals. The construction industry has explored the use of hybrid dispute resolution methods, such as the combination of arbitration and mediation, known as